BIOFILM FORMATION IN EXTRA INTESTINAL PATHOGENIC Escherichia coli STRAIN: RELATIONSHIP WITH ANTIMICROBIAL RESISTANCE AND PATIENTS CLINICAL OUTCOME - ARINDAM CHAKRABORTY; PRABHA ADHIKARI; SHALINI SHENOY (International Journal of Pharma and Bio Sciences, 2013)
Extraintestinal pathogenic Escherichia coli infection is a serious health threat in the world. They show a high degree of resistance in various groups of antibiotics as biofilm production is one of the causes of antibiotic resistance. The aim of the present study is to detect in vitro biofilm formation by ExPEC isolates and resistance pattern of commonly used antibiotic, and patient’s clinical outcome. A total of 300 isolates were screened for biofilm formation by the method described by O’Toole and kolter. Haemolysin production was tested on 5% sheep blood agar. Production of Extended spectrum-β-lactamases (ESBL) was detected by combination of disk diffusion method and in the same way AmpC was detected by AmpC disk test. Carbapenemase production was detected by modified Hodge test. Identification of Metallo- β- lactamases (MBL) activity was performed by MBL Etest. Of the 300 isolates 129 (43%) were biofilm producers. Twenty eight percent of the biofilm producing isolates showed clear zone of haemolysis in blood agar plate. Out of 129 isolates 72% were ESBL producers, ampC type β lactamase production were seen 31% isolates. Among the other group of antibiotics most number of resistance were seen in ciprofloxacin (73%). Most active antibiotic were amikacin and carbapenem class of drugs. Seventy and half percent patients were improved with proper antibiotic treatment were as relapses/ re-infection were seen in 14% patients and mortality seen in 11% patients. Biofilm producing isolates are associated with high level of drug resistance, mortality and relapses. They are producing ESBL, ampC along with carbapenemases which is a major problem worldwide. Early use of appropriate empirical antibiotic will probably reduce the mortality and morbidity of the patients.